Peningkatan Kemandirian Belajar Melalui Problem Based Learning (PBL) Berbantuan Media Video Interaktif Pada Mata Pelajaran Spreadsheet Di SMK Negeri 1 Sukoharjo - Zahroh, Fatimatuz; Nurhaini, Lies (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2024)
This research aims to find out whether there is an increase in learning independence by using the Problem Based Learning (PBL) learning method assisted by Interactive Video Media in class X Accounting and Financial Institution (AKL) students at SMK Negeri 1 Sukoharjo. This research uses a quasi-experimental design with a nonequivalent control group design research model. The population in this study were class X AKL students at SMK Negeri 1 Sukoharjo. Samples were taken using cluster sampling. The samples in this study were students in class The data collection techniques used were questionnaires and observation. Data analysis uses Normality Test, Homogeneity Test, and Independent Sample t-test. The results of this research show that there is an increase in learning independence using the Problem Based Learning (PBL) method assisted by interactive video media for students at SMK Negeri 1 Sukoharjo as proven by the t-test with Sig. (2-tailed) is 0.000 < 0.05. Learning independence using PBL assisted by interactive video media is higher than learning independence using PBL assisted PPT. This is proven by the posttest results of the experimental and control classes with the majority of the experimental class being in the interval 158 - 162, while the majority of the control class is in the interval 115 - 124. Keywords: Problem Based Learning (PBL), Interactive Video, Independent Learning, Spreadsheet.